PENGGUNAAN KONSELING INDIVIDUAL DENGAN METODE ISLAMI UNTUK MENINGKATKAN KEMATANGAN EMOSI DALAM MENGHADAPI PERILAKU AGRESIF [USING INDIVIDUAL COUNSELING WITH ISLAMIC METHODS TO INCREASE EMOTIONAL MATURITY IN THE FACE OF AGGRESSIVE BEHAVIOR] - Urrohmah, Aulia; Nurjannah, N (Acta Islamica Counsenesia: Counselling Research and Applications, 2022)
This study aims to describe the stages of individual counseling with Islamic methods in increasing emotional maturity in dealing with aggressive behavior. The research method uses qualitative-action. The data collection techniques used in this study were observation, interviews, and documentation. The data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results obtained are that the client already has an awareness of the emotions felt, and the client is able to carry out the task of being patient and always grateful when feeling or experiencing excessive feelings, but the client feels it is not easy in the process.